Literature and Consolation Fictions of Comfort - Pieters, Jürgen (Edinburgh University Press, 2022)
Provides a deeper understanding of the comforts of reading literatureHistory of the concept of consolationReadings of canonical works (Homer, Dante, Shakespeare, Flaubert)Critical analysis of bibliotherapyChapter on contemporary writers and thinkers (Roland Barthes, Denise Riley, Julian Barnes) who have written on 'grief'By focusing on a number of significant moments in the interlocking histories of the book's two central concepts--literature and consolation--this study makes readers aware of the premises that underlie the assumption that literary writings can bring comfort. What is it in literary texts that provides this special experience? How does literature help us to understand what consolation means and the effects it can have on individual readers? The intersecting ideas of literature and consolation in Homer, Dante, Shakespeare and Flaubert through to Roland Barthes, Denise Riley and Julian Barnes, guide today's readers on how literature provides examples, food for thought and good companionship in times of grief and pain. Taking its cue from the rich history of consolatory thinking, the book shows how writers from different times have explored the potential of their writing to offer solace. The result of these explorations, this book argues, has shaped the history of Western literature decisively